Teaching Outside the Box: How to Grab Your Students By Their Brains - Johnson LouAnne (Jossey-Bass, 2005)
From seating plans to Shakespeare, Teaching Outside the Box offers practical strategies that will help both new teachers and seasoned veterans create dynamic classroom environments where students enjoy learning and teachers enjoy teaching. This indispensable book is filled with no-nonsense advice, checklists, and handouts as well as